Halophilic Pectinase-Producing Bacteria from Arthrocnemum macrostachyum Rhizosphere: Potential for Fruit–Vegetable Juice Processing - Amal S. Alswat; Ohud Muslat Alharthy; Seham Saeed Alzahrani; Seham Sater Alhelaify (Microorganisms)
This study aimed to isolate salt-tolerant pectinolytic bacteria from the rhizosphere of a salt marsh plant and utilize their pectinases for the clarification of detox juice preparation. Sixteen halophilic bacterial strains were isolated from the rhizospheric soil of Arthrocnemum macrostachyum. The isolates were screened for pectinase activity, and two strains, ASA21 and ASA29, exhibited the highest pectinase production in the presence of 2.5% NaCl, reaching 13.3 and 14.1 IU mL−1, respectively. The strains were identified as Bacillus paralicheniformis and Paenibacillus sp. by 16S rDNA sequencing and phylogenetic analysis. Growth kinetics and pectinase production studies revealed that both strains produced pectinase during the log phase, with ASA29 demonstrating higher growth and pectinase titers. The pectinase from ASA29 exhibited enhanced activity in the presence of 3% NaCl. The pectinases from both strains were applied for the clarification of detox juice prepared from beetroot, carrots, and apples. The use of 20 IU mL−1 pectinase from ASA29 for 2–3 h yielded > 96% juice with high total phenolic content and antioxidant activities. This study highlights the potential of salt-tolerant pectinolytic bacteria from the rhizosphere for biotechnological applications, particularly in the clarification of juices with high salt content.